AN ANALYSIS OF FACTORS INFLUENCING THE PROVISION OF PENTAVALENT IMMUNISATION IN KAPUAS KANAN HULU URBAN VILLAGE - Novin Yetiani; Lea Masan, Yunida Haryanti, Aditiya Sardi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
Pentavalent immunisation was carried out simultaneously in Indonesia in February 2014 in West Java, the immunisation coverage until July was above the average target. Immunisation of DPT-HB-Hib 1 from the target coverage of 57.2% turned out to be 59.3%, DPT-HB-Hib 2 from the target of 55.4% the coverage was 57.9%, DPT-HB-Hib 3 from the target of 52.5% through July coverage was more than 57.8%. This study used an analytical survey with a cross sectional approach carried out in April 2018. The sample of this study was 50 mothers who had babies aged 2-4 months. Data analysis was performed using Chi-Square. The results showed that there was a correlation between knowledge (p = 0.035), attitude (p= 0.039) and Health Officer Support (p= 0.034) with the provision of Pentavalent Immunization in Kapuas Kanan Hulu Village in the Work Area of Puskesmas Sungai Durian Sintang. The health care can focus more on providing information about Pentavalent Immunisation and fostering the desire of the community to immunise their babies by motivating people to maintain the health and development of their children.